2017
DOI: 10.1093/hmg/ddx290
|View full text |Cite
|
Sign up to set email alerts
|

Maternal BMI at the start of pregnancy and offspring epigenome-wide DNA methylation: findings from the pregnancy and childhood epigenetics (PACE) consortium

Abstract: Pre-pregnancy maternal obesity is associated with adverse offspring outcomes at birth and later in life. Individual studies have shown that epigenetic modifications such as DNA methylation could contribute. Within the Pregnancy and Childhood Epigenetics (PACE) Consortium, we meta-analysed the association between pre-pregnancy maternal BMI and methylation at over 450,000 sites in newborn blood DNA, across 19 cohorts (9,340 mother-newborn pairs). We attempted to infer causality by comparing the effects of matern… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
177
5
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 240 publications
(196 citation statements)
references
References 90 publications
12
177
5
2
Order By: Relevance
“…However, we cannot rule out the possibility that some overlapping CpGs could be involved in biologic pathways linking smoking to the well-established consequence of shorter gestational length [94]. Other potential confounders not accounted for in this study such as maternal obesity and alcohol intake may influence offspring DNA methylation although we have found in the PACE consortium that their impact on methylation [95,96] is very modest compared with maternal smoking in pregnancy which was included in our models.…”
Section: Discussionmentioning
confidence: 84%
“…However, we cannot rule out the possibility that some overlapping CpGs could be involved in biologic pathways linking smoking to the well-established consequence of shorter gestational length [94]. Other potential confounders not accounted for in this study such as maternal obesity and alcohol intake may influence offspring DNA methylation although we have found in the PACE consortium that their impact on methylation [95,96] is very modest compared with maternal smoking in pregnancy which was included in our models.…”
Section: Discussionmentioning
confidence: 84%
“…83 Similarly, maternal BMI has been linked to methylation levels of several loci in the cord blood, the majority of which persist into adolescence independent of paternal BMI and gestational weight gain. 203,204 Studies focusing on immune cells have demonstrated that high maternal BMI is inversely correlated with methylation levels within the promoter of inflammatory genes in cord blood mononuclear cells 205 that persisted for up to 3 years of age. 206 Recent studies carried out using targeted bisulfite sequencing in purified cord blood monocytes demonstrated that pregravid maternal obesity is associated with DNA hypomethylation, particularly at promoters of transcription factors such as PPARG that are associated with a dampened transcriptional responses to LPS.…”
Section: Mechanisms Linking Maternal Obesity and Fetal Immune Dysfuncmentioning
confidence: 99%
“…members have begun cataloguing-omics signatures of early-life factors that could be associated with CC. 29,30 These signatures will be analysed across the different I4C cohorts with available biological samples. This work will complement the I4C questionnaire-based epidemiological investigations and may provide mechanistic insights into CC aetiology.…”
Section: Publicationsmentioning
confidence: 99%